Pemodelan Sistem Manajemen Arsip Berbasis Workflow Untuk Mendukung Tata Kelola Dokumen - Cici Melisma; Armansyah Armansyah (Fakultas Teknik Universitas Persada Indonesia YAI, 2026)
Records management at the North Sumatra Provincial Regional Revenue Agency faces various challenges, such as a lack of integration in document recording processes, manual records management workflows, inefficient document retrieval, and the risk of record loss or damage. These issues highlight the need for a records management system capable of enhancing document management efficiency and supporting structured records governance. This study aims to develop a workflow-based records management system model to serve as a reference for developing a digital records management system. Research data were collected through observation, interviews, and a review of existing records management processes. The study employed the Prototyping development method, encompassing requirements analysis, business process modeling using Business Process Model and Notation (BPMN), system modeling using Unified Modeling Language (UML), database design using Entity Relationship Diagrams (ERD), and interface prototype development using Figma. The study produced a system model, database design, and interface prototype, all of which were validated for alignment with business processes and user requirements. Validation results indicate that all functional requirements are accommodated within the proposed model, enabling it to systematically represent the records management process and serve as a viable reference for developing a digital records management system.